2003
DOI: 10.1212/01.wnl.0000055433.55136.55
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin for the treatment of postherpetic neuralgia

Abstract: Treatment of PHN with pregabalin is safe, efficacious in relieving pain and sleep interference, and associated with greater global improvement than treatment with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
385
2
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 709 publications
(411 citation statements)
references
References 42 publications
11
385
2
9
Order By: Relevance
“…This assessment time point has also been used in a number of pregabalin trials (Dworkin et al., 2003; Sabatowski et al., 2004). The established primary efficacy endpoint of ≥30% pain relief, as measured by the NPRS score, was employed.…”
Section: Methodsmentioning
confidence: 99%
“…This assessment time point has also been used in a number of pregabalin trials (Dworkin et al., 2003; Sabatowski et al., 2004). The established primary efficacy endpoint of ≥30% pain relief, as measured by the NPRS score, was employed.…”
Section: Methodsmentioning
confidence: 99%
“…Dworkin et al 83 have demonstrated in a randomized placebo-controlled trial that, for patients with PHN, pregabalin-treated patients at doses of 300 or 600 mg each day had significantly reduced pain by the first day of treatment, and that by the end of this eight-week study the proportion of patients achieving at least 30%, or at least 50%, pain relief was significantly higher in those patients treated with pregabalin. In a separate randomized controlled PHN trial, Sabatowski et al 84 found that, at a dose of 300 mg/day compared with placebo, patients receiving pregabalin not only had significant pain reduction but also enjoyed improvement in sleep and mood.…”
Section: Pregabalinmentioning
confidence: 96%
“…In addition to intensity, pain is known to have different sensory and affective qualities that can be measured to de- 20,21 Recently, a revised version of the SF-MPQ, the SF-MPQ-2, has been published. 22 The major advantage of the SF-MPQ-2 is the addition of descriptors specific to neuropathic pain.…”
Section: Pain Qualitymentioning
confidence: 99%